Celiac disease as differential diagnosis of normocalcemic hyperparathyroidism - Pedro Weslley Rosario (Sociedade Brasileira de Patologia Clínica, 2020)
ABSTRACT There is no recommendation to investigate celiac disease (CD) in patients with elevated parathyroid hormone (PTH) and normal blood calcium if they are asymptomatic, especially if they do not have hypovitaminosis D. CD was diagnosed in a 30-year-old asymptomatic man without vitamin D deficiency, who had total calcium 9.2 mg/dl, 25-hydroxyvitamin D 36 ng/dl, PTH 112 pg/ml, total IgA 42 mg/dl, anti-tissue transglutaminase (tTG) IgA 22 U/ml. Duodenal biopsy by endoscopy confirmed CD. The patient started a gluten-free diet that was maintained. After six months, the patient had total calcium 9.5 mg/dl, 25-hydroxyvitamin D 42 ng/dl, and PTH 48 pg/ml. In most patients with elevated PTH and normal blood calcium, clinical history, assessment of renal function, vitamin D and phosphorus measurement, and calciuria define the cause of secondary hyperparathyroidism. However, in the few cases in which this initial investigation is negative, even asymptomatic individuals should be tested for CD antibodies before the diagnosis of normocalcemic primary hyperparathyroidism is made.